Effects of Lithology Combination Compaction Seepage Characteristics on Groundwater Prevention and Control in Shallow Coal Seam Group Mining - Kaijun Miao; Shihao Tu; Wenping Li; Jinghua Li; Jinhu Tian; Hongbin Zhao; Jieyang Ma (Applied Sciences, 2025)
The mining of shallow coal seam groups triggers mine water inrush and ecological environment destruction. Effective groundwater prevention and control requires controlling the compaction and seepage characteristics (CSCs) of broken rock in goaf. In this study, the CSCs of roof lithology and goaf broken rock combinations are experimentally investigated. The results indicate that, for samples with identical gradation, the percentage of void (PV) is minimized in sandstone–mudstone combinations, while PV increases with higher coal content. Initial compaction of composite samples is primarily governed by soft rock re-crushing, whereas the stable compaction stage is determined by the initial PV. Under low axial stress, the CSCs of lithological combination samples exhibit instability, with the mudstone layer reducing flow velocity by approximately 36% under equivalent compaction and seepage conditions. Particle migration, leading to the blockage of the seepage section, is an important cause of the decrease in permeability. Based on experimental findings, a stress–void–seepage coupling model is established to describe the compaction–seepage behavior of lithologic combination broken rock in shallow goafs.